Perspektif Semiotika Roland Barthes terhadap Penyimpangan Perilaku Sosial dalam Film Dilan 1990 - ali mahfud, robit (Icon: Islamic Communication and Contemporary Media Studies, 2025)
This study examines the representation of deviant social behavior in the film Dilan 1990 using Roland Barthes’ semiotic analysis. The research aims to explore the denotative, connotative, and mythological meanings embedded in scenes that depict deviant behavior, particularly among adolescents. This is a qualitative-descriptive study employing semiotic analysis of visual and narrative elements in the film. The findings reveal that denotatively, Dilan’s behavior often violates norms of politeness and discipline; connotatively, these acts are interpreted as symbols of courage and youthful romance; while at the mythological level, the film constructs a patriarchal ideology that portrays dominant male figures as the romantic ideal. These findings suggest that popular films play a role in shaping social perceptions of deviant behavior and highlight the need for critical examination to prevent normalization of actions that contradict societal values.